Crosslinked polymers and processes of ethylene and monocyclic organosiloxanes
Through the combination of ethylene/monocyclic organosiloxane copolymer and free radical distributor, a crosslinked structure is formed, which solves the problems of low catalytic rate and many by-products during the persulfation process, and achieves more efficient catalysis and better material properties.
Patent Information
- Application Number
- JP2023504108
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-07-29
- Publication Date
- 2025-03-19
- Estimated Expiration
- 2040-07-29
AI Technical Summary
The existing low-density polyethylene (LDPE) has low catalytic rate and low production efficiency during the persulfation process, and there are many by-products in the persulfation products, which affects the performance of the material.
An ethylene/monocyclic organosiloxane (MOCOS) copolymer was used, and a free radical distributor was added to form a crosslinked ethylene/monocyclic organosiloxane copolymer through heating reaction, with a crosslinking degree of more than 70%.
The persulfation catalytic rate and production efficiency are improved, the generation of by-products is reduced, and the thermal stability and operability of the material are significantly improved.
Smart Images

Figure 0007649372000001 
Figure 0007649372000002 
Figure 0007649372000003
Abstract
Description
[Background technology]
[0001] Polyethylene is the most widely used thermoplastic material today. In some applications, it is necessary to modify polyethylene to enhance certain properties. For example, crosslinking between polymer chains forms a three-dimensional (3D) network structure that improves heat resistance, providing crosslinked polyethylene with a higher operating temperature. Peroxide curing is widely used industrially to crosslink polyethylene. For example, crosslinkable polyethylene (XLPE), which is composed of low-density polyethylene (LDPE), peroxide, and antioxidant, is widely used as an insulation material for medium-voltage (MV), high-voltage (HV), and extra-high-voltage (EHV) wire and cable applications. In wire and cable applications, typically, an inner semiconductive layer, an XLPE insulation layer, and an outer semiconductive layer are coated onto the conductor through a crosshead in a triple extrusion process. Then, the cable core, which is composed of the conductor, the inner semiconductive layer, the XLPE insulation layer, and the outer semiconductive layer, is passed through a vulcanizing tube with 10 bar N2 pressure to initiate the peroxide crosslinking. After cooling by passage through a cooling tube, the cable core is placed in a chamber at elevated temperature (eg, 70° C.) to remove decomposed by-products from the peroxide.
[0002] Thus, there is a recognized need in the art for LDPEs with improved peroxide cure that improves productivity by increasing cure speed and reduces peroxide loading (and reduces by-products). Thus, there is a further recognized need in the art for LDPEs with improved peroxide cure response, not only for XLPE insulation applications, but also for other peroxide crosslinkable compositions. Summary of the Invention
[0003] The present disclosure provides a process, in one embodiment, comprising providing (A) an ethylene / MOCOS copolymer consisting of (i) units derived from ethylene, (ii) 0.01% to 0.5% by weight of units derived from a comonomer, and (iii) optionally units derived from a termonomer. The comonomer has formula (I): [R 1 ,R 2 SiO 2 / 2 ] n [In the formula, n is an integer of 3 or more, Each R 1 are independently (C2-C4) alkenyl or H2C=C(R 1a )-C(=O)-O-(CH2) m - and R 1a is H or methyl, m is an integer from 1 to 4; Each R 2 are independently H, (C1-C4) alkyl, phenyl, or R 1 The process includes mixing (B) a free radical initiator with (A) an ethylene / MOCOS copolymer to form a mixture. The process includes heating the mixture and forming a crosslinkable ethylene / MOCOS copolymer composition. In one embodiment, the process includes crosslinking the crosslinkable ethylene / MOCOS copolymer composition to form a crosslinked ethylene / MOCOS copolymer composition having a gel content of greater than 70%.
[0004] The present disclosure provides a composition. In one embodiment, a crosslinkable composition is provided, the composition comprising: A) an ethylene copolymer having: (i) units derived from ethylene; (ii) 0.01% to 0.5% by weight of units derived from a comonomer, and (iii) optionally, units derived from a termonomer, the comonomer being of formula (I) [R 1 ,R 2 SiO 2 / 2 ] n [In the formula, n is an integer of 3 or more, Each R 1 are independently (C2-C4) alkenyl or H2C=C(R 1a )-C(=O)-O-(CH2) m - and R 1a is H or methyl, m is an integer from 1 to 4; Each R 2 are independently H, (C1-C4) alkyl, phenyl, or R 1 and an ethylene copolymer, which is a monocyclic organosiloxane (MOCOS) of the formula: and (B) a free radical initiator. After crosslinking, the crosslinkable composition forms a crosslinked ethylene / MOCOS copolymer composition having a gel content of greater than 70%.
[0005] definition Any reference to the Periodic Table of the Elements is to that published by CRC Press, Inc., 1990-1991. References to element groups in this table are by the new notation for numbering groups.
[0006] For purposes of United States patent practice, the contents of any referenced patent, patent application, or publication are incorporated by reference in their entirety (or the equivalent U.S. version thereof is so incorporated by reference), particularly with respect to disclosure of definitions (to the extent not inconsistent with any definitions specifically provided in this disclosure).
[0007] Numerical ranges disclosed herein include all values between and including the lower and upper limits, and in the case of ranges containing explicit values (e.g., 1 or 2, or 3-5, or 6, or 7), all subranges between any two explicit values are included (e.g., the range 1-7 above includes subranges 1-2, 2-6, 5-7, 3-7, 5-6, etc.).
[0008] Unless specifically stated to the contrary, implicit from the context, or customary in the art, all parts and percentages are by weight and all testing methods are current as of the filing date of this disclosure.
[0009] As used herein, an “acrylate” has the following structure (A):
[0010] [ka] [In the formula, R1 is a hydroxyl group or a C1-C 18 and R2 is H or CH3. Acrylate monomers include acrylates and methacrylates.
[0011] As used herein, the term "blend" or "polymer blend" refers to a mixture of two or more polymers. A blend may or may not be miscible (not phase separated at the molecular level). A blend may or may not be phase separated. A blend may or may not contain one or more domain configurations as determined from transmission electron spectroscopy, light scattering, x-ray scattering, and other methods known in the art. A blend may be made by physically mixing two or more polymers at a macro level (e.g., melt blending or compounding of resins) or at a micro level (e.g., co-forming in the same reactor).
[0012] The term "composition" refers to a mixture of materials that comprise the composition, as well as reaction products and decomposition products formed from the materials of the composition.
[0013] The terms "comprising," "including," "having," and their derivatives are not intended to exclude the presence of any additional component, step, or procedure, whether specifically disclosed or not. For the avoidance of doubt, all compositions claimed through the use of the term "comprising" may include any additional additive, adjuvant, or compound, whether polymeric or otherwise, unless specifically stated to the contrary. In contrast, the term "consisting essentially of" excludes any other component, step, or procedure from the scope of any succeeding description, except those that are not essential to operability. The term "consisting of" excludes any component, step, or procedure not expressly delineated or listed. The term "or" refers to the listed members individually as well as in any combination, unless otherwise stated. The use of the singular includes the use of the plural, and vice versa.
[0014] An "ethylene-based polymer" is a polymer that contains greater than 50 weight percent (wt%) polymerized ethylene monomer (based on the total amount of polymerizable monomers) and, optionally, may contain at least one comonomer. Ethylene-based polymers include ethylene homopolymers and ethylene copolymers (meaning units derived from ethylene and one or more comonomers). The terms "ethylene-based polymer" and "polyethylene" may be used interchangeably.
[0015] As used herein, the term “ethylene monomer” or “ethylene” refers to a chemical unit having two carbon atoms with a double bond between them, and each carbon bonded to two hydrogen atoms, that can be polymerized with other such chemical units to form an ethylene-based polymer composition.
[0016] A "hydrocarbon" is a compound containing only hydrogen and carbon atoms. A "hydrocarbonyl" (or "hydrocarbonyl group") is a hydrocarbon having a valency (typically monovalent). The hydrocarbon can have a linear, cyclic, or branched structure.
[0017] As used herein, the term “linear low density polyethylene” (or “LLDPE”) refers to a polymer having units derived from ethylene and at least one C3-C 10 LLDPE refers to linear ethylene / α-olefin copolymers containing a heterogeneous distribution of short chain branches comprising units derived from an α-olefin or a C4-C8 α-olefin comonomer. LLDPE is characterized by the presence of little, if any, long chain branching, in contrast to conventional LDPE. LLDPE has a density of less than 0.910 g / cc to 0.940 g / cc. Non-limiting examples of LLDPE include TUFLIN™ Linear Low Density Polyethylene Resins (available from The Dow Chemical Company), DOWLEX™ Polyethylene Resins (available from the Dow Chemical Company), and MARLEX™ Polyethylene (available from Chevron Phillips).
[0018] As used herein, the term "low density polyethylene" (or LDPE) refers to polyethylene having a density of 0.910 g / cc to less than 0.940 g / cc, or 0.918 g / cc to 0.930 g / cc, and long chain branching with a broad molecular weight distribution (MWD), i.e., a "broad MWD" of 4.0 to 20.0.
[0019] An "olefin" is an unsaturated aliphatic hydrocarbon containing a carbon-carbon double bond.
[0020] The term "phenyl" (or "phenyl group") is a C6H5 aromatic hydrocarbon ring having a valency (typically monovalent).
[0021] The term "polymer" or "polymeric material" as used herein refers to a compound prepared by polymerizing monomers, whether of the same or different types, to provide in polymerized form the multiple and / or repeating "units" or "mer units" that make up the polymer. Thus, the term polymer in general encompasses the term homopolymer, which is commonly used to refer to a polymer prepared from only one type of monomer, and the term copolymer, which is commonly used to refer to a polymer prepared from at least two types of monomer. It also encompasses all forms of copolymers, e.g., random, block, etc. The terms "ethylene / α-olefin polymer" and "propylene / α-olefin polymer" refer to the above-mentioned copolymers prepared from polymerizing ethylene or propylene, respectively, with one or more additional polymerizable α-olefin monomers. It should be noted that although polymers are often referred to as "made of" one or more particular monomers, "based on" a particular monomer or monomer type, "containing" a particular monomer content, etc., in this context, the term "monomer" is understood to refer to the polymerized residue of a particular monomer and not to the unpolymerized species. Generally, polymers are referred to herein in terms of "units" that are the polymerized form of the corresponding monomers.
[0022] Test Method Density is measured according to ASTM D792, Method B. Results are reported in grams per cubic centimeter (g / cc).
[0023] Fourier Transform Infrared Analysis ("FTIR") The amount of terminal and internal trans double bonds per 1000 carbons ("1000C") was determined by Fourier transform infrared analysis ("FTIR"). Sample films (approximately 250-300 micrometers thick) used for FTIR analysis were compression molded by pressing approximately 0.5 g pellets of sample in a Carver hydraulic press with heated platens set at 190°C. The amount of terminal and internal alkenes per 1000 carbons was measured following a procedure similar to that outlined in ASTM method D6248. FTIR measures internal alkene bonds in the trans configuration; internal alkene bonds in the cis configuration cannot be detected by FTIR.
[0024] Gel Content Gel content was measured according to ASTM D2765-01. Samples were hand cut into small pellets (approximately 1 mm x 1 mm x 1 mm cubes) from 1 mm thick polymer plaques prepared on a hot press (120°C for 10 minutes (min), followed by preheating at 180°C / 10 MPa for 20 minutes, then cooling to room temperature (RT) under 10 megapascal (MPa) pressure for 10 minutes). Samples were refluxed in xylene for 12 hours (h). After 6 hours, hot xylene was removed and then new fresh xylene was added and continued reflux for another 6 hours. Gel content results are reported in percent (%). A higher gel content indicates a higher level of crosslinking.
[0025] Gel Permeation Chromatography (GPC) The chromatographic system consisted of a PolymerChar GPC-IR (Valencia, Spain) high temperature GPC chromatograph equipped with an internal IR5 infra-red detector (IR5) and a 4-capillary viscometer (DV) coupled to a Precision Detectors (now Agilent Technologies) 2-angle laser light scattering (LS) detector model 2040. For all absolute light scattering measurements, a 15 degree angle is used for the measurements. The autosampler oven compartment was set at 160° Celsius and the column compartment was set at 150° Celsius. The columns used were four Agilent "Mixed A" 30 cm, 20 micron linear mixed bed columns. The chromatography solvent used was 1,2,4 trichlorobenzene (CAS120-82-1, HPLC grade, Fisher Scientific) containing 200 ppm of butylated hydroxytoluene (BHT). The solvent source was nitrogen sparged. The injection volume used was 200 microliters and the flow rate was 1.0 milliliters / minute.
[0026] Calibration of the GPC column set was performed with at least 20 narrow molecular weight distribution polystyrene standards with molecular weights ranging from 580 to 8,400,000, arranged in six "cocktail" mixtures with at least 10 intervals between each individual molecular weight. Standards were purchased from Agilent Technologies. Polystyrene standards were prepared at 0.025 grams in 50 milliliters of solvent for molecular weights of 1,000,000 and above, and at 0.05 grams in 50 milliliters of solvent for molecular weights below 1,000,000. The polystyrene standards were dissolved at 80 degrees Celsius for 30 minutes with gentle agitation. The peak molecular weights of the polystyrene standards were converted to polyethylene molecular weights using Equation 1 (as described in Williams and Ward, J. Polym. Sci., Polym. Let., 6, 621 (1968)).
[0027]
number
[0028] A polynomial between the third and fifth order was used to fit each of the polyethylene equivalent calibration points, and A was adjusted slightly (from approximately 0.375 to 0.440) to correct for column resolution and band broadening effects such that the homopolymer polyethylene standard had a molecular weight of 120,000.
[0029] Total plate counts of the GPC column set were performed using Eicosane (prepared at 0.04 g in 50 milliliters of TCB and dissolved for 20 minutes with gentle agitation). Plate counts (Equation 2) and symmetry (Equation 3) were measured with a 200 microliter injection according to the following equations:
[0030]
number
[0031]
number
[0032] Samples were prepared in a semi-automated fashion using the PolymerChar "Instrument Control" software to target sample weight of 2 mg / ml and add solvent (containing 200 ppm BHT) via the PolymerChar high temperature autosampler to a pre-nitrogen sparged septa-capped vial. Samples were dissolved at 160 degrees Celsius under "slow" shaking for 2 hours.
[0033] Mn (GPC) , Mw (GPC) , and Mz (GPC) The calculation was based on GPC results using PolymerChar GPCOne™ software, baseline-subtracted IR chromatograms at each equally spaced data collection point (i), and the polyethylene equivalent molecular weights obtained from a narrow standard calibration curve at point (i) in Equation 1, according to Equations 4-6, using the internal IR5 detector (measurement channel) of the PolymerChar GPC-IR chromatograph.
[0034]
number
[0035] To monitor deviations over time, a flow rate marker (decane) was introduced into each sample via a micropump controlled by the PolymerChar GPC-IR system. This flow rate marker (FM) was used to linearly correct the pump flow rate (flow rate (apparent)) of each sample by RV matching the respective decane peak in the sample (RV (FM sample)) with that of the decane peak in the narrow standard calibration (RV (FM calibrated)). Any change in time of the decane marker peak is then assumed to be related to a linear shift in flow rate (flow rate (effective)) throughout the run. To facilitate the highest accuracy of the RV measurement of the flow rate marker peak, a least squares fitting routine is used to fit the peaks of the flow rate marker concentration chromatogram to a quadratic equation. The first derivative of the quadratic equation is then used to solve for the true peak position. After calibrating the system based on the flow rate marker peak, the effective flow rate (relative to the narrow reference calibration) is calculated as Equation 7. Processing of the flow rate marker peaks was performed via PolymerChar GPCOne™ software. Acceptable flow corrections are those that bring the effective flow rate within + / - 2% of the apparent flow rate. Flow (effective) = Flow (apparent) x (RV(FM calibrated) / RV(FM sampled)) (Equation 7)
[0036] Triple Detector GPC (TDGPC) The chromatographic system, analytical conditions, column set, column calibration and calculation and distribution of conventional molecular weight moments were performed according to the methods described in Gel Permeation Chromatography (GPC).
[0037] With regard to the determination of the viscometer and light scattering detector offsets from the IR5 detector, a systematic approach for the determination of multiple detector offsets was performed in a manner consistent with that published by Balke, Mourey et al. (Mourey and Balke, Chromatography Polym. Chpt 12, (1992)) (Balke, Thitiratsakul, Lew, Cheung, Mourey, Chromatography Polym. Chpt 13, (1992)) using PolymerChar GPCOne™ software to optimize triple detector log (MW and IV) results from broad homopolymer polyethylene standards (Mw / Mn>3) against narrow standard column calibration results from a narrow standard calibration curve.
[0038] Absolute molecular weight data were obtained using PolymerChar GPCOne™ software in a manner consistent with that published by Zimm (Zimm, BH, J. Chem. Phys., 16, 1099 (1948)) and Kratochvil (Kratochvil, P., Classical Light Scattering from Polymer Solutions, Elsevier, Oxford, NY (1987)). The total injected concentration used in determining the molecular weight was obtained from the mass detector area and mass detector constant derived from a suitable linear polyethylene homopolymer or one of the polyethylene standards of known weight average molecular weight. The calculated molecular weight (using GPCOne™) was obtained using the light scattering constant and refractive index concentration coefficient, dn / dc, of 0.104, derived from one or more of the polyethylene standards described below. In general, the mass detector response (IR5) and light scattering constant (determined using GPCOne™) should be determined from a linear standard with a molecular weight greater than about 50,000 g / mol. Viscometer calibration (determined using GPCOne™) can be accomplished using the method described by the manufacturer, or alternatively, by using published values of a suitable linear standard, such as Standard Reference Material (SRM) 1475a (available from the National Institute of Standards and Technology, NIST). A viscometer constant (obtained using GPCOne™) is calculated that relates the specific viscosity area (DV) and injected mass for the calibration standard to its intrinsic viscosity. The chromatographic concentration is assumed to be low enough to preclude addressing the second viral coefficient effect (concentration effect on molecular weight).
[0039] Absolute weight average molecular weight (MW (Abs)) is obtained (using GPCOne™) from the light scattering (LS) area integrated chromatogram (factored by the light scattering constant) divided by the mass recovered from the mass constant and the mass detector (IR5) area. The molecular weight and intrinsic viscosity responses are linearly extrapolated (using GPCOne™) at the chromatographic end where the signal to noise is low. Each of the other moments Mn (Abs) and Mz (Abs) is calculated according to Equations 8-9 as follows:
[0040]
number
[0041] gpcBR branching index by triple detector GPC (3D-GPC) The gpcBR branching index is determined by first calibrating the light scattering, viscosity, and concentration detectors as described above. A baseline is then subtracted from the light scattering, viscometer, and concentration chromatograms. An integration window is then set to ensure that all of the low molecular weight retention volume ranges of the light scattering and viscometer chromatograms that indicate the presence of detectable polymer from the infrared (IR5) chromatogram are integrated. Linear polyethylene standards are then used to establish the Mark-Houwink constants for polyethylene and polystyrene. After obtaining the constants, the two values are used to construct a conventional calibration method with two linear references for polyethylene molecular weight and polyethylene intrinsic viscosity as a function of elution volume, as shown in equations (10) and (11).
[0042]
number
[0043] The gpcBR branching index is a robust method for characterizing long chain branching, as described in Yau, Wallace W., "Examples of Using 3D-GPC-TREF for Polyolefin Characterization", Macromol.Symp., 2007, 257, 29-45. This index avoids the "slice-by-slice" 3D-GPC calculations traditionally used in determining g' values and calculating branching frequency in favor of the entire polymer detector area. From the 3D-GPC data, the bulk absolute weight average molecular weight (Mw,Abs) of the sample can be obtained by the light scattering (LS) detector using a peak area method. This method avoids the "slice-by-slice" ratio of the light scattering detector signal to the concentration detector signal, as required in traditional g' determination.
[0044] 3D-GPC also independently obtains the intrinsic viscosity of the sample using equation (8). The area calculations in equations (5) and (8) provide greater accuracy because the sample area as a whole is much less susceptible to detector noise at the baseline and integration limits and to variations caused by the 3D-GPC settings. More importantly, the peak area calculations are not affected by detector volume offsets. Similarly, the intrinsic viscosity (IV) of the sample is obtained with high accuracy by the area method shown in equation (12).
[0045]
number
[0046] To determine the gpcBR branching index, the light scattering elution area of the sample polymer is used to determine the molecular weight of the sample. The elution area of the viscosity detector for the sample polymer is used to determine the intrinsic viscosity (IV or [η]) of the sample.
[0047] First, the molecular weight and intrinsic viscosity for a linear polyethylene standard, such as SRM1475a or equivalent, are determined using conventional calibrations for both molecular weight and intrinsic viscosity as a function of elution volume ("cc").
[0048]
number
[0049] All statistics with a "cc" subscript are determined using the respective dissolution volume, the corresponding conventional calibration as described above, and the concentration (Ci). Values without subscripts are measurements based on the mass detector, LALLS, and viscometer area. PE The values of α and Log K are iteratively adjusted until the linear reference sample has a gpcBR measurement of zero. For example, the final values of α and Log K for determining the gpcBR in this particular case are 0.725 and -3.391, respectively, for polyethylene, and 0.722 and -3.993, respectively, for polystyrene. These polyethylene coefficients were then entered into Equation 13.
[0050] Once the K and α values have been determined using the procedure above, the procedure is repeated using the branched samples that are analyzed using the final Mark-Houwink constants obtained from the linear reference when the best "cc" calibration value is applied.
[0051] The interpretation of gpcBR is straightforward. For linear polymers, the values measured by LS and viscometer will be close to conventional calibration standards, so the gpcBR calculated from equation (14) will be close to zero. For branched polymers, the measured polymer molecular weight will be higher than the calculated Mw,cc, and the calculated IVcc will be higher than the measured polymer IV, especially at high levels of long chain branching, so the gpcBR will be higher than zero. In fact, the gpcBR value represents the fractional change in IV due to the molecular size shrinkage effect as a result of polymer branching. A gpcBR value of 0.5 or 2.0 represents a molecular size shrinkage effect in IV at a level of 50% and 200%, respectively, for an equivalent weight of linear polymer molecules.
[0052] In these particular examples, the advantage of using gpcBR compared to conventional "g' index" and branching frequency calculations is due to the higher accuracy of gpcBR. All of the parameters used in the determination of the gpcBR index are obtained with high accuracy and are not adversely affected by the low 3D-GPC detector response at high molecular weights from the concentration detector. Errors in the alignment of the detector volumes also do not affect the accuracy of the gpcBR index determination.
[0053] High Temperature Creep The conditions of IEC 60811-2-1, section 9.1 were followed. Dumbbell bars as specified in Figure 12 of IEC 60811-1-1 were cut from cross-linked compression moulded plaques of 1 mm thickness. The dumbbell bars were subjected to a load of 20 N / cm after 20 minutes at 200 °C. 2 High temperature creep under load was tested. High temperature creep measures the elongation under load and the results are reported as a percentage (%). The value indicates the degree of crosslinking, with lower numbers indicating higher levels of crosslinking.
[0054] Melt Index As used herein, the term "melt index" or "MI" refers to a measure of how easily a thermoplastic polymer flows when in a molten state. Melt index, or I2, is measured according to ASTM D 1238, condition 190°C / 2.16 kg, and is reported in grams dissolved per 10 minutes (g / 10 min). I10 is measured according to ASTM D 1238, condition 190°C / 10 kg, and is reported in grams dissolved per 10 minutes (g / 10 min).
[0055] Moving Die Rheometer (MDR) Testing MDR testing was performed on an MDR2000 (Alpha Technologies) at 180°C for 20 minutes while monitoring the change in torque according to ASTM D5289-12, Standard Test Method for Rubber Property-Vulcanization Using Rotorless Cure Meters. The minimum measured torque value is indicated as "ML" expressed in deciNewton-meter (dN-m). As the curing or crosslinking progresses, the measured torque value increases and eventually reaches a maximum torque value. The maximum or highest measured torque value is indicated as "MH" expressed in dN-m. All other conditions being equal, the higher the MH torque value, the higher the degree of crosslinking. The T90 crosslinking time is determined as the number of minutes required to achieve a torque value equal to 90% of the difference between MH minus ML (MH-ML), i.e., 90% of the way from ML to MH. The shorter the T90 crosslinking time, i.e., the faster the torque value is 90% of the way from ML to MH, the faster the cure rate of the test specimen. Conversely, the longer the T90 crosslinking time, i.e., the longer it takes for the torque value to gain 90% of the way from ML to MH, the slower the cure rate of the test sample.
[0056] Nuclear magnetic resonance ( 1 H NMR) As used herein, the term "nuclear magnetic resonance" or "NMR" or "proton NMR" refers to the spectral analysis of a material or compound that provides information about the chemical composition and structure of the material or compound. Samples for proton NMR were prepared using 0.1-0.2 g of sample in 3.25 g of 30 / 70 wt / wt o-dichlorobenzene-d4 / perchloroethylene (ODCB-d4 / PCE) containing 0.001 M chromium(III) acetylacetonate, Cr(AcAc)3 prepared in a 10 mm tube. Samples were heated at 115°C and vortexed to ensure homogeneity. Single pulse proton spectra were acquired on a Bruker AVANCE 600 MHz spectrometer equipped with a Bruker high temperature CryoProbe and a sample temperature of 120°C. Spectra were acquired with a ZG pulse P1=20us (90°PW), 64 scans, AQ1.82 sec, D115 sec.
[0057] The amount of Si-CH3 per 1000 carbons and Si-CH=CH2 groups (also referred to interchangeably as "Si-vinyl") per 1000 carbons was obtained as described above. 1 The H NMR spectrum was determined. The total polymer protons were quantified by integrating from approximately -0.5 ppm to 3 ppm, which was set to a value of 2000, thus representing 1000 carbons. The signals from the three Si-vinyl protons appear as three separate multiplets from approximately 5.8 ppm to 6.1 ppm. The closest to 5.8 ppm (D Vi The )4 multiplet overlaps partially with one of the LDPE chain end vinyl protons at about 5.76 ppm, therefore only the two multiplets at about 5.92 ppm and 6.02 ppm are integrated and averaged to obtain the moles of Si-vinyl per 1000 carbons. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0058] 1. Process The present disclosure provides a process. In one embodiment, the process includes providing (A) an ethylene / MOCOS copolymer. The ethylene / MOCOS copolymer comprises (i) units derived from ethylene, (ii) from 0.01% to 0.5% by weight of units derived from a comonomer, and (iii) optionally, units derived from a termonomer. The comonomer has formula (I): [R 1 ,R 2 SiO 2 / 2 ] n [In the formula, n is an integer of 3 or more, Each R 1 are independently (C2-C4) alkenyl or H2C=C(R 1a )-C(=O)-O-(CH2) m - and R 1a is H or methyl, m is an integer from 1 to 4; Each R 2 are independently H, (C1-C4) alkyl, phenyl, or R 1 is a monocyclic organosiloxane (MOCOS). The process includes mixing (B) a free radical initiator with (A) an ethylene / MOCOS copolymer to form a mixture. The process includes heating the mixture for a period of time to form a crosslinkable ethylene / MOCOS copolymer composition.
[0059] In one embodiment, the process includes heating a crosslinkable composition at a curing temperature for a period of time and forming a crosslinked ethylene / MOCOS copolymer composition having a gel content greater than 70%.
[0060] The process includes providing an ethylene / MOCOS copolymer, which is an ethylene-based polymer that contains (i) units derived from ethylene, (ii) units derived from a comonomer, and (iii) optionally, units derived from a termonomer. The comonomer has formula (I): [R 1 ,R2 SiO 2 / 2 ] n [In the formula, n is an integer of 3 or more, Each R 1 are independently (C2-C4) alkenyl or H2C=C(R 1a )-C(=O)-O-(CH2) m - and R 1a is H or methyl, m is an integer from 1 to 4; Each R 2 are independently H, (C1-C4) alkyl, phenyl, or R 1 is a monocyclic organosiloxane (MOCOS).
[0061] Ethylene-based polymers containing monocyclic organosiloxanes (MOCOS) of formula (I) are interchangeably referred to as "ethylene / MOCOS copolymers" and, when a termonomer is present, ethylene-based polymers containing monocyclic organosiloxanes (MOCOS) of formula (I) are interchangeably referred to as "ethylene / MOCOS / terpolymers" where ethylene units constitute the majority (wt%) of the monomers present in the polymer. In other words, the ethylene-based polymer composition comprises ethylene monomer, MOCOS comonomer (and optional termonomer), and each of the two monomers (or each of the three monomers, if a termonomer is present) polymerizes into the polymer backbone. Thus, the ethylene / MOCOS copolymers (and / or ethylene / MOCOS / terpolymers) are structurally different compared to polyethylenes containing functional coagents pendantly grafted to the polymer chain. The weight percent of the MOCOS comonomer is based on the total weight of the ethylene / MOCOS copolymer (or the total weight of the ethylene / MOCOS / terpolymer, if a termonomer is present).
[0062] The ethylene / MOCOS copolymer contains, in addition to ethylene, units derived from a comonomer. The comonomer is a monocyclic organosiloxane of formula (I) [R 1 ,R 2 SiO 2 / 2 ]n (interchangeably referred to as "MOCOS" or "MOCOS comonomers"), wherein formula (I) is a molecule containing a single ring substructure made up of alternating silicon and oxygen atoms, which contains an unsaturated organo(hydrocarbonyl) group and optionally hydrogen ("H"), saturated, or aromatic substituents. Each of the at least two unsaturated organic groups and at least two silicon atoms in the ring substructure has at least one unsaturated organic group bonded to it, and any remaining valences of the silicon atoms after being occupied by the unsaturated organic groups and oxygen atoms are bonded to hydrogen atoms, saturated, or aromatic substituents, or aggregates of such molecules.
[0063] MOCOS can be a monocyclic organosiloxane composed of a 6-membered ring (n=3), an 8-membered ring (n=4), a 10-membered ring (n=-5), or a 12-membered ring (n=6). The ring moiety is represented by the formula (I): [R 1 ,R 2 SiO 2 / 2 ] n [In the formula, n is an integer of 3 or more, or n is from 3 or 4 to 5 or 6; Each R 1 are independently (C2-C4) alkenyl or H2C=C(R 1a )-C(=O)-O-(CH2) m - and R 1a is H or methyl, Each R 2 are independently H, (C1-C4) alkyl, phenyl, or R 1 Each [R 1 ,R 2 SiO 2 / 2 ] units, R 1 Groups and R 2 The groups are bonded to their respective silicon atoms. The units are simply D using the conventional organosiloxane abbreviations. R1,R2 As a result, formula (I) is represented as [D R1,R2 ] n Then, R 1 and R 2may be the same or different.
[0064] Non-limiting examples of compounds suitable for MOCOS of formula (I) include: Vi,Et where Vi is vinyl and Et is ethyl, R 1 is vinyl and R 2 is ethyl; MOCOS is abbreviated as D アリル,Et In the case of R 1 is an aryl group and R 2 is ethyl; MOCOS is abbreviated as D ブテニル,Et In the case of R 1 is butenyl (H2C=C(H)CH2CH2-), and R 2 is ethyl; MOCOS is abbreviated as D Vi,Vi In the case of R 1 is vinyl and R 2 is vinyl; MOCOS is abbreviated as D アリル,アリル In the case of R 1 is an aryl group and R 2 is an allyl; the abbreviation for MOCOS is D ブテニル,ブテニル In the case of R 1 is butenyl (H2C=C(H)CH2CH2-), and R 2 is butenyl; MOCOS is abbreviated as D Vi,Ph where Ph is phenyl, R 1 is vinyl and R 2 is phenyl; MOCOS is abbreviated as D アリル,Ph In the case of R 1 is an aryl group and R 2 is phenyl; MOCOS is abbreviated as D ブテニル,Ph In the case of R 1 is butenyl (H2C=C(H)CH2CH2-), and R 2 is phenyl.
[0065] R 2 If is methyl (CH3), the unit is more simply D R1 As a result, formula (I) is represented as [D R1 ] nFurther non-limiting examples of compounds suitable for MOCOS of formula (I) include: Vi In the case of R 1 is vinyl and R 2 is methyl; MOCOS is abbreviated as D アリル In the case of R 1 is an aryl group and R 2 is methyl; MOCOS is abbreviated as D ブテニル In the case of R 1 is butenyl (H2C=C(H)CH2CH2-), and R 2 is methyl.
[0066] In one embodiment, each R of MOCOS of formula (I) 1 are independently H2C=C(R 1a )-C(=O)-O-(CH2) m -[wherein, R 1a is H or methyl, and the subscript m is an integer from 1 or 2 to 3 or 4, and any range or individual value therein. 2 are independently (C1-C2) alkyl or (C2-C3) alkenyl, or each R 2 are independently (C1-C2) alkyl, or each R 2 is independently methyl.
[0067] In one embodiment, the MOCOS of formula (I) has the following structure (B):
[0068] [ka] 2,4,6-trimethyl-2,4,6-trivinyl-cyclotrisiloxane, "(D Vi )3 (CAS number 3901-77-7).
[0069] In one embodiment, the MOCOS of formula (I) has the following structure (C):
[0070] [ka] 2,4,6,8-tetramethyl-2,4,6,8-tetravinyl-cyclotetrasiloxane, "(D Vi )4 (CAS number 2554-06-5).
[0071] In one embodiment, the MOCOS of formula (I) is 2,4,6,8,10-pentamethyl-2,4,6,8,10-pentavinyl-cyclopentasiloxane, (D Vi )5.
[0072] The MOCOS comonomer of formula (I) is present in the ethylene-based polymer in an amount from 0.01 weight percent to 2 weight percent, or from 0.01 weight percent to 0.5 weight percent, or from 0.05 weight percent to 0.45 weight percent, or from 0.1 weight percent to 0.40 weight percent, or from 0.3 weight percent to 0.5 weight percent, or from 0.15 weight percent to 0.30 weight percent, or from 0.05 weight percent to 0.15 weight percent. The weight percentages are based on the total weight of the ethylene-based polymer composition, i.e., the ethylene / MOCOS copolymer.
[0073] In addition to ethylene and MOCOS comonomers, the ethylene / MOCOS copolymer includes units derived from an optional termonomer, making it an ethylene / MOCOS / terpolymer. When present, the termonomer is an olefin, an unsaturated ester, a functionalized alkene, a silane, and combinations thereof. Non-limiting examples of suitable termonomers (when present) include propylene, C4-C8 α-olefins, acrylates, (meth)acrylates, vinyl acetate, vinyltrimethoxysilane, and combinations thereof. When a termonomer is present in the ethylene-based polymer, the termonomer is present in an amount of 0.5% to 50% by weight, or 1% to 40% by weight, or 1% to 30% by weight, or 1% to 25% by weight, or 1% to 20% by weight, or 1% to 15% by weight, or 3% to 12% by weight, or 5% to 10% by weight. The weight percentage is based on the total weight of the ethylene / MOCOS / terpolymer. S
[0074] In one embodiment, the ethylene-based polymer composition comprises an ethylene / MOCOS copolymer of formula (I) and formula (II): Formula (II) [R 1 ,R 2 SiO 2 / 2 ] n [In the formula, n is an integer of 3 or more, Each R 1 are independently a methyl group, a (C2-C4) alkenyl, or H2C=C(R 1a )-C(=O)-O-(CH2) m - but with at least two R 1 is not a methyl group, R 1a is H or methyl, m is an integer from 1 to 4; Each R 2 are independently H, (C1-C4) alkyl, phenyl, or R 1 It also includes the termonomer:
[0075] In one embodiment, the ethylene / MOCOS copolymer (and / or ethylene / MOCOS / terpolymer) may be a component in an ethylene-based polymer composition that includes one or more optional additives. When additives are present, non-limiting examples of suitable additives include stabilizers, light stabilizers, UV absorbers, antioxidants, plasticizers, antistatic agents, voltage stabilizers, crosslinking coagents, and scorch retarders, pigments, dyes, carbon black, nanoparticles, nucleating agents, fillers, lubricants, flame retardants, processing aids, smoke suppressants, viscosity control agents, and antiblocking agents. The ethylene-based polymer composition may, for example, include one or more additives and fillers in a combined weight of less than 70 percent based on the weight of the ethylene-based polymer composition.
[0076] In one embodiment, the ethylene-based polymer composition is formulated with one or more antioxidants.Non-limiting examples of suitable antioxidants include bis(4-(1-methyl-1-phenylethyl)phenyl)amine (e.g., NAUGARD 445), 2,2-methylene-bis(4-methyl-6-t-butylphenol) (e.g., VANOX MBPC), 2,2'-thiobis(2-t-butyl-5-methylphenol (CAS No. 90-66-4, CAS No. 96-69-5, commercially available LOWINOX TBM-6), 2,2'-thiobis(6-t-butyl-4-methylphenol (CAS No. 90-66-4, commercially available LOWINOX TBM-6), and 2,2'-thiobis(6-t-butyl-4-methylphenol) (CAS No. 90-66-4, commercially available LOWINOX TBM-6). TBP-6), tris[(4-tert-butyl-3-hydroxy-dimethylphenyl)methyl]-1,3,5-triazine-2,4,6-trione) (e.g., CYANOX 1790), pentaerythritol tetrakis(3-(3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl)propionate (e.g., IRGANOX 1010, CAS number 6683-19-8), 3,5-bis(1,1-dimethylethyl)-4-hydroxybenzenepropanoic acid 2,2'-thiodiethadiyl ester (e.g., IRGANOX 1035, CAS number 41484-35-9), distearyl thiodipropionate ("DSTDP"), dilauryl thiodipropionate (e.g., IRGANOX PS 800), stearyl 3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate (e.g., IRGANOX 1076), 2,4-bis(dodecylthiomethyl)-6-methylphenol (IRGANOX 1726), 4,6-bis(octylthiomethyl)-o-cresol (e.g., IRGANOX 1520), and 2',3-bis[[3-[3,5-di-tert-butyl-4-hydroxyphenyl]propionyl]]propionohydrazide (IRGANOX 10 24), 4,4-thiobis(2-t-butyl-5-methyiphenoi) (also known as 4,4'-thiobis(6-tert-butyl-m-cresol)), 2,2'-thiobis(6-t-butyl-4-methylphenol, tris[(4-tert-butyl-3-hydroxy-2,6-dimethylphenyl)methyl]-1,3,5-triazine-2,4,6-trione; distearyl thiodipropionate, and combinations thereof.The antioxidant is present in an amount of from 0.01 weight percent to 1.5 weight percent, or from 0.05 weight percent to 1.2 weight percent, or from 0.07 weight percent to 1.0 weight percent, or from 0.1 weight percent to 0.5 weight percent, based on the total weight of the ethylenic composition. The ethylenic polymer composition is treated with the antioxidant prior to the heating step.
[0077] In one embodiment, the ethylene-based polymer composition is an ethylene / MOCOS copolymer comprising: (i) ethylene and (ii) from 0.05 wt.% to 0.5 wt.% (D Vi )3, (D Vi ) 4, and (D Vi and a MOCOS copolymer selected from the group consisting of ethylene / MOCOS copolymers selected from the group consisting of ethylene / MOCOS copolymers having a Mw / Mn of 5.0 to 9.5 or 7.5 to 9.5, a vinyl content of 0.3600 / 1000 carbon atoms to 0.6200 / 1000 carbon atoms, a trans content of 0.1000 / 1000 carbon atoms to 0.3100 / 1000 carbon atoms, and a MI of 2.0 g / 10 min to 5.0 g / 10 min.
[0078] In one embodiment, the ethylene-based polymer composition comprises (i) ethylene and (ii) 0.05 wt.% to 0.5 wt.% of (D Vi and 4, wherein the ethylene / MOCOS copolymer composition has one, some, or all of the following properties: (i) an Mw / Mn of 5.0 to 9.5 or 7.5 to 9.5, and / or (ii) a vinyl content of from 0.3600 / 1000 carbon atoms to 0.6200 / 1000 carbon atoms; and / or (iii) a trans content of from 0.1000 / 1000 carbon atoms to 0.3100 / 1000 carbon atoms; and / or (iv) MI of 2.0 g / 10 min to 5.0 g / 10 min or 2.5 g / 10 min to 4.7 g / 10 min.
[0079] In one embodiment, the ethylene-based polymer composition is an ethylene / MOCOS copolymer comprising: (i) ethylene and (ii) from 0.1 wt. % to 0.5 wt. % (D Viand a MOCOS copolymer selected from 4.) ethylene / MOCOS copolymers having a Mw / Mn of 7.0 to 7.5, a vinyl content of 0.5800 / 1000 carbons to 0.6200 / 1000 carbons, a trans content of 0.2000 / 1000 carbon atoms to 0.2500 / 1000 carbon atoms, and a MI of 35.0 g / 10 min to 42.0 g / 10 min.
[0080] In one embodiment, the ethylene-based polymer composition is an ethylene / MOCOS / MA terpolymer consisting of (i) ethylene, (ii) from 0.01% to 0.5% by weight MOCOS, and (iii) from 1% to 50% by weight MA, or from 8% to 12% by weight MA, where the weight percentages are based on the total weight of the ethylene / MOCOS / MA terpolymer.
[0081] The process includes mixing (B) a free radical initiator with (A) an ethylene / MOCOS copolymer to form a mixture. In one embodiment, the free radical initiator is an organic peroxide. An organic peroxide is a molecule, or a collection of such molecules, that contains carbon atoms, hydrogen atoms, and two or more oxygen atoms and has at least one -OO- group, where if there is more than one -OO- group, each -OO- group is indirectly bonded to another -OO- group through one or more carbon atoms. Non-limiting examples of suitable organic peroxides include diacyl peroxides, peroxycarbonates, peroxydicarbonates, peroxyesters, peroxyketals, cyclic ketone peroxides, dialkyl peroxides, ketone peroxides, and combinations thereof.
[0082] The organic peroxides are represented by the formula R O -OOR O [In the formula, each R O are independently 20 ) alkyl group or (C6-C 20 Each of the (C1 to C) aryl groups may be a monoperoxide. 20 ) alkyl groups are independently unsubstituted or have one or two (C6-C 12) substituted with an aryl group. 20 The aryl group is unsubstituted or has one to four (C1-C 10 ) alkyl group. Alternatively, the organic peroxide may be of the formula R O -OOROOR O [In the formula, R is (C2 to C 10 ) alkylene, (C3-C 10 ) a divalent hydrocarbon group such as cycloalkylene or phenylene, and each R O is as defined above.
[0083] Non-limiting examples of suitable organic peroxides include dicumyl peroxide, lauryl peroxide, benzoyl perbenzoate, tert-butyl perbenzoate, di(tert-butyl)peroxide, cumene hydroperoxide; 2,5-dimethyl-2,5-di(t-butyl-peroxy)hexyne-3, 2,5-di-methyl-2,5-di(t-butyl-peroxy)hexane, tert-butyl hydroperoxide, isopropyl percarbonate, α,α'-bis(tert-butylperoxy) Diisopropylbenzene, t-butylperoxy-2-ethylhexyl-monocarbonate, 1,1-bis(t-butylperoxy)-3,5,5-trimethylcyclohexane, 2,5-dimethyl-2,5-dihydroxyperoxide, t-butylcumyl peroxide, α,α'-bis(t-butylperoxy)-p-diisopropylbenzene, bis(1,1-dimethylethyl)peroxide, bis(1,1-dimethylpropyl)peroxide, 2,5-dimethyl-2,5-bis(1,1-dimethylethylperoxide) 1,1-bis(1,1-dimethylethylperoxy)-3,3,5-trimethylcyclohexane, 2,5-dimethyl-2,5-bis(1,1-dimethylethylperoxy)hexyne, 4,4-bis(1,1-dimethylethylperoxy)valeric acid, butyl ester, 1,1-bis(1,1-dimethylethylperoxy)-3,3,5-trimethylcyclohexane, benzoyl perbenzoate, tert-butyl peroxybenzoate, di-tert-amyl peroxide ("DTAP"), bis(alpha-t-butyl-peroxyisopropyl)benzene ("BIPB"), isopropyl alcohol, Examples of such peroxides include propyl cumyl t-butyl peroxide, t-butyl cumyl peroxide, di-butyl butyl peroxide, 2,5-bis(t-butylperoxy)-2,5-dimethylhexane, 2,5-bis(t-butylperoxy)-2,5-dimethylhexyne-3,1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, isopropyl cumyl cumyl peroxide, butyl 4,4-di(tert-butylperoxy)valerate, and di(isopropyl cumyl)peroxide.
[0084] Non-limiting examples of suitable commercially available organic peroxides include TRIGONOX manufactured by AkzoNobel and LUPEROX manufactured by Arkema.
[0085] In one embodiment, the free radical initiator is an organic peroxide that is dicumyl peroxide (DCP).
[0086] The mixing of the ethylene / MOCOS copolymer (A) and the free radical initiator (B) is carried out by placing pellets of the ethylene / MOCOS copolymer and the free radical initiator, optionally together with an antioxidant, in a container. The container is then shaken, rotated, tumbled, or otherwise agitated so that the free radical initiator is held in contact with the ethylene / MOCOS copolymer pellets or otherwise absorbed into the ethylene / MOCOS copolymer pellets. The process includes heating the mixture of (A) the ethylene / MOCOS copolymer and (B) the free radical initiator at a temperature of from 60° C. or 65° C. to 70° C. or 75° C. or 80° C., or otherwise above the melting temperature of the peroxide. Heating of the mixture is carried out for a period of from 1 minute, or 10 minutes, or 30 minutes to 1 hour, or 2 hours, or 3 hours, or 4 hours, or 5 hours, or 6 hours, or 7 hours, or 8 hours, thereby allowing the free radical initiator to diffuse into the pellets of ethylene / MOCOS copolymer.
[0087] In one embodiment, the mixing and heating are performed sequentially.
[0088] In one embodiment, the mixing and heating are performed simultaneously.
[0089] The process includes crosslinking (interchangeably referred to as "curing") the crosslinkable ethylene / MOCOS copolymer composition and forming a crosslinked ethylene / MOCOS copolymer composition having a gel content greater than 70%. In one embodiment, the crosslinked ethylene / MOCOS copolymer has a gel content of from 71%, or 75%, or 80% to 85%, or 90%, or 95%, or 99%. In further embodiments, the crosslinked ethylene / MOCOS copolymer has a gel content of 71-99%, or 72-95%, or 73-90%.
[0090] The curing step (crosslinking step) involves heating the crosslinkable ethylene / MOCOS copolymer composition at a curing temperature of greater than 100°C, or 110°C, or 125°C, up to 150°C, or 180°C, or 200°C for a period of 1 minute, or 5 minutes, or 10 minutes, or 30 minutes, or from 1 hour to 2 hours, or 5 hours, or 7 hours, or more, to form a crosslinked ethylene / MOCOS copolymer composition having a gel content of 71% to 99%, or 72% to 95%, or 73 to 90%.
[0091] Crosslinking of the ethylene / MOCOS copolymer can be accomplished by a procedure that does not utilize a peroxide initiator. In one embodiment, the process includes subjecting the ethylene / MOCOS copolymer to irradiation and forming a crosslinked ethylene / MOCOS copolymer having a gel content of greater than 70%. The irradiation can be electron beam irradiation (E-beam), ultraviolet (UV) irradiation, photoinitiation, and combinations thereof. In this embodiment, the described mixing and heating steps are eliminated and replaced with an irradiation step. The crosslinked ethylene / MOCOS copolymer has a gel content of greater than 70%, or 71%, or 75%, or 80% to 85%, or 90%, or 95%, or 99%. In further embodiments, the crosslinked ethylene / MOCOS copolymer has a gel content of 71%-99%, or 72%-95%, or 73%-90%.
[0092] In one embodiment, the process includes mixing 3% to 0.05% by weight of a free radical initiator (B) with 97% to 99.95% by weight of an ethylene / MOCOS copolymer (A). The process includes heating the mixture at a temperature of 70° C. to 90° C. and forming a crosslinkable ethylene / MOCOS copolymer. The process includes curing the crosslinkable ethylene / MOCOS copolymer composition and forming a crosslinked ethylene / MOCOS copolymer composition having, after curing, a T90 of less than 5 minutes or a T90 of 3.0 minutes to 4.9 minutes and a gel content of 71% to 99%.
[0093] In one embodiment, the process includes mixing 1.5% to 0.5% by weight of a free radical initiator (B) with 98.5% to 99.5% by weight of an ethylene / MOCOS copolymer (A). The ethylene / MOCOS copolymer (A) has 0.3% to 0.5% by weight (based on the total weight of the ethylene / MOCOS copolymer) of units derived from the MOCOS comonomer. The process includes heating the mixture at a temperature of 70° C. to 90° C. for 0.5 to 8 hours to form a crosslinkable ethylene / MOCOS copolymer composition. The process includes curing the crosslinkable ethylene / MOCOS copolymer composition to form a crosslinked ethylene / MOCOS copolymer composition having a gel content of 71% to 99% and a high temperature creep elongation of 20% to 50%.
[0094] In one embodiment, the process includes mixing 1.5% to 0.5% by weight of a free radical initiator (B) with 98.5% to 99.5% by weight of an ethylene / MOCOS copolymer (A). The ethylene / MOCOS copolymer has 0.05% to 0.2% by weight (based on the total weight of the ethylene / MOCOS copolymer) of units derived from the MOCOS comonomer. The process includes heating the mixture at a temperature of 70° C. to 90° C. for 2 to 6 hours to form a crosslinkable ethylene / MOCOS copolymer composition. The process includes curing the crosslinkable ethylene / MOCOS copolymer composition to form a crosslinked ethylene / MOCOS copolymer composition having a gel content of 71% to 99% and a high temperature creep elongation of 50% to 90%.
[0095] In one embodiment, the process includes mixing 3% to 0.3% by weight of a free radical initiator (B) with 97% to 99.7% by weight of an ethylene / MOCOS copolymer (A) and 0.05% to 0.3% by weight of one or more antioxidants (resulting in a 100% by weight crosslinkable ethylene-based polymer composition). The process includes heating the mixture at a temperature of 70° C. to 90° C. for 2 to 6 hours and forming a crosslinkable ethylene-based copolymer composition. After curing, a crosslinked ethylene / MOCOS copolymer composition is formed having: (1) a gel content between 64% and 99% and a T90 between 3.0 minutes and 5.3 minutes; or (2) A gel content of 71% to 99% and a T90 of less than 5 minutes or a T90 of 3.0 minutes to 4.9 minutes.
[0096] 2. Composition The present disclosure provides a composition that is a crosslinkable ethylene-based polymer composition. A "crosslinkable ethylene-based polymer composition," as used herein, is a composition that contains an ethylene-based polymer and one or more additives (e.g., a free radical initiator or an organic peroxide) that enhance the ability of the ethylene-based polymer to crosslink when subjected to crosslinking conditions (e.g., heat, irradiation, and / or UV light). After being subjected to crosslinking conditions (e.g., "post-crosslinking" or "post-curing"), the crosslinkable ethylene-based polymer composition becomes a "crosslinked ethylene-based polymer composition" that is structurally and physically distinct from the crosslinkable ethylene-based polymer composition.
[0097] In one embodiment, the crosslinked ethylenic composition is formed by a peroxide-initiated process as previously disclosed herein.
[0098] In one embodiment, a crosslinkable ethylene-based polymer composition is provided that includes: (A) an ethylene copolymer comprised of: (i) units derived from ethylene; (ii) from 0.01% to 0.5% by weight of units derived from a comonomer; and (iii) optionally, units derived from a termonomer. The comonomer is represented by formula (I): [R 1 ,R 2 SiO 2 / 2 ] n [In the formula, n is an integer of 3 or more, Each R 1 are independently (C2-C4) alkenyl or H2C=C(R 1a )-C(=O)-O-(CH2) m - and R 1a is H or methyl, m is an integer from 1 to 4; Each R 2 are independently H, (C1-C4) alkyl, phenyl, or R 1(ethylene / MOCOS copolymer). The crosslinkable ethylene-based polymer composition also includes (B) a free radical initiator. The crosslinkable ethylene / MOCOS copolymer composition, after crosslinking, forms a crosslinked ethylene / MOCOS copolymer having a gel content of greater than 70%. In one embodiment, the crosslinked ethylene / MOCOS copolymer composition has a gel content of 71%, or 75%, or 80% to 85%, or 9%, or 95%, or 99%. In further embodiments, the crosslinked ethylene / MOCOS copolymer composition has a gel content of 71%-99%, or 72%-95%, or 73%-90%.
[0099] In one embodiment, the MOCOS comonomer for the ethylene / MOCOS copolymer is 2,4,6-trimethyl-2,4,6-trivinyl-cyclotrisiloxane (D Vi )3, 2,4,6,8-tetramethyl-2,4,6,8-tetravinyl-cyclotetrasiloxane (D Vi ) 4, 2,4,6,8,10-pentamethyl-2,4,6,8,10-pentavinyl-cyclotrisiloxane (D Vi ) 5, and combinations thereof.
[0100] In one embodiment, the MOCOS comonomer for the ethylene / MOCOS copolymer is (D Vi The crosslinked ethylene / MOCOS copolymer composition is 0.01 wt % to 0.5 wt % (D Vi ) 4, and the crosslinked ethylene / MOCOS copolymer composition has one, some, or all of the following properties: (i) a Mw / Mn of 7.5 to 9.5, and / or (ii) a vinyl content of 0.3600 / 1000 carbons to 0.6200 / 1000 carbons, and / or (iii) A trans content of 0.1000 / 1000 carbon atoms to 0.3100 / 1000 carbon atoms.
[0101] In one embodiment, the crosslinkable ethylene-based polymer composition comprises (A) 97% to 99.95% by weight of an ethylene / MOCOS copolymer and (B) 3% to 0.05% by weight of a free radical initiator, wherein the weight percentages are based on the total weight of the crosslinked ethylene / MOCOS copolymer composition.
[0102] In one embodiment, the crosslinkable ethylene-based polymer composition comprises 98.5% to 99.5% by weight of an ethylene / MOCOS copolymer (A). The ethylene / MOCOS copolymer has 0.3% to 0.5% by weight of units derived from a MOCOS comonomer (based on the total weight of the ethylene / MOCOS copolymer). The crosslinkable ethylene-based polymer composition also comprises 1.5% to 0.5% by weight of a free radical initiator (B). The crosslinkable ethylene / MOCOS copolymer composition, after crosslinking, forms a crosslinked ethylene / MOCOS copolymer composition having a gel content of 71% to 99%, or 72% to 95%, or 73% to 90%, and has a high temperature creep elongation of 20% to 50%.
[0103] In one embodiment, the crosslinkable ethylene-based polymer composition comprises 98.5% to 99.5% by weight of ethylene / MOCOS copolymer (A). The ethylene / MOCOS copolymer has 0.05% to 0.2% by weight of units derived from the MOCOS comonomer (based on the total weight of the ethylene / MOCOS copolymer). The crosslinkable ethylene-based polymer composition also comprises 1.5% to 0.5% by weight of a free radical initiator (B). The crosslinkable ethylene / MOCOS copolymer composition, after crosslinking, forms a crosslinked ethylene / MOCOS copolymer composition having a gel content of 71% to 99%, or 72% to 95%, or 73% to 90%, and has a high temperature creep elongation of 50% to 90%.
[0104] In one embodiment, the crosslinkable ethylene-based polymer composition comprises 98.5% to 99.5% by weight of ethylene / MOCOS copolymer (A). The ethylene / MOCOS copolymer has 0.05% to 0.2% by weight of units derived from the MOCOS comonomer (based on the total weight of the ethylene / MOCOS copolymer). The crosslinkable ethylene-based polymer composition also comprises 1.5% to 0.5% by weight of a free radical initiator (B). The crosslinkable ethylene-based polymer composition comprises 0.05% to 0.3% by weight of one or more antioxidants (resulting in 100% by weight of the crosslinkable ethylene-based polymer composition). The crosslinkable ethylene-based polymer composition, after crosslinking, forms a crosslinked ethylene / MOCOS copolymer composition having one, some, or all of the following properties: (i) a gel content of between 64% and 99%, or between 71% and 99%, or between 72% and 95%, or between 73% and 90%, and / or (ii) a T90 of 3.0 minutes to 5.3 minutes or 3.0 minutes to 4.9 minutes, and / or (ii) High temperature creep elongation of 50% to 90%.
[0105] Purpose The crosslinked ethylene / MOCOS copolymer compositions can be used in a variety of applications including, but not limited to, wire and cable applications such as insulation layers for AC (alternating current) and DC (direct current) MV / HV / EHV cables, carbon black filled semiconducting layers for MV / HV / EHV cables, accessories for power distribution transmission lines, insulation layers, insulating encapsulation films for photovoltaic (PV) modules, etc.
[0106] By way of example and not by way of limitation, several embodiments of the present disclosure will now be detailed in the following examples. EXAMPLES
[0107] The materials used in the examples are described in Table 1 below.
[0108] [Table 1]
[0109] 1. Polymerization of Ethylene and MOCOS Comonomer The amounts of each material used in the samples and comparative samples (controls) are provided in Table 2 below. A 545 milliliter (mL) stirred autoclave was charged with ethylene, MOCOS ((D Vi A mixture of propylene (as a chain transfer agent) and organic peroxide (Luperox 26) as a 0.5%, 1%, or 2% by weight solution in odorless mineral spirits is added to the mixture as a polymerization initiator and is heated to approximately 28,000 psi (1,969 kg / cm). 2 The reactor was subjected to a set pressure of 200 rpm for 10 min. The reactor temperature was set at a target temperature of 220° C. Ethylene / MOCOS copolymers were continuously synthesized under the polymerization conditions shown in Table 2 and then converted to pellet form by melt extrusion. The conditions listed in Table 2 are averages over the length of time the samples were collected. The "autoclave made" experimental reactor copolymers thus formed were found to have the characteristics listed in Table 3.
[0110] [Table 2]
[0111] The properties of the resulting ethylene / MOCOS copolymers are provided in Table 3 below.
[0112] [Table 3] NM=not measurable, * - based on the total weight of the ethylene-based polymer composition (D Vi ) 4 wt.% and MA wt.%; + Vinyl and trans are in mole percent.
[0113] [Table 4] *ID=identification information, the first value in the closing brackets is (D Vi ) 4% by weight, and the second value is the MI.
[0114] Proton NMR was used to determine the (D Vi The degree of incorporation / conversion of 4 was characterized. Proton NMR detects the presence of Si-CH3 and Si-vinyl. On average, D Vi 41 molecules incorporate 2.5 double bonds into the polyethylene backbone (Table 5). Without wishing to be bound by any particular theory, (D Vi It is believed that copolymerization of 4 with ethylene and incorporation of two double bonds produces H-branched structures that result in an unexpected increase in melt strength.
[0115] [Table 5]
[0116] 2. Crosslinked ethylene polymer composition In the inventive example (IE), dicumyl peroxide (DCP) and ethylene / MOCOS copolymer pellets (and optional antioxidant) were weighed into a 250 mL fluoride HDPE bottle. The bottle was then shaken for about 5 seconds for mixing. The bottle was then placed in an oven at 80° C. The bottle was then removed every 5 minutes (min) for shaking six times at 0, 5, 10, 15, 20, and 25 minutes (each shaking time was about 5 seconds). The bottle was then shaken five times and then placed in the oven for 6.5 hours. The MDR was then measured.
[0117] In the comparative sample (CS), DCP, LDPE pellets, and free (D Vi)4 was weighed into a 250 mL fluoride HDPE bottle. The bottle was then shaken for approximately 5 seconds for mixing. The bottle was then placed in an oven at 80° C. The bottle was then removed every 5 minutes (min) for shaking six times at 0, 5, 10, 15, 20, and 25 minutes (each shaking time was approximately 5 seconds). The bottle was then shaken five times and then placed in the oven for 6.5 hours. The MDR was then measured. For the comparative sample, (D Vi )4 and LDPE.
[0118] [Table 6] * ID=identification information, the first value in the closing brackets is (D Vi ) 4% by weight, the second value is MI, c=control;
[0119] [Table 7] * ID=identification information, the first value in the closing brackets is (D Vi ) 4% by weight, the second value is MI, C=control, S=sample
[0120] Tables 6A to 6B show the ethylene / (D Vi ) 4 copolymers as additives to LDPE, with equal amounts of free (D Vi Tables 6A-6B, 7A-7B, 8, and 9 provide side-by-side comparisons showing that the crosslinking level (greater than 70% gel content) of a given (D Vi ) ethylene with 4 wt.% comonomer content / (D Vi Each of the inventive examples containing a LDPE and free (D)4 copolymer was Vi ) 4 is compared with a comparative sample consisting of (D Vi ) 4 The weight percent of comonomer is the free (D Vi) the same or substantially the same as the weight percent of 4. The peroxide content is the same across each side-by-side comparison. For each side-by-side comparison, the inventive examples have (i) higher MH-ML values, and / or (ii) shorter T90 times, and / or (iii) greater percent gel content, and / or (iv) lower high temperature creep values than the comparative samples.
[0121] Tables 7A-7B (below) show crosslinked compositions containing the antioxidant Irganox 1076 (referred to as 1076 in the data tables).
[0122] [Table 8] * ID=identification information, the first value in the closing brackets is (D Vi ) 4% by weight, the second value is MI, C=control, S=sample
[0123] [Table 9] * ID=identification information, the first value in the closing brackets is (D Vi ) 4% by weight, the second value is MI, c=control;
[0124] [Table 10]
[0125] [Table 11] * 0.15% AO Blend = antioxidant blend of 0.06% Cyanox 1790, .09% DSTDP, and 19 ppm Uvinul 4050 (at 0.15 wt % aggregates based on the total weight of the crosslinkable ethylene-based polymer composition).
[0126] The high temperature creep data from Tables 8-9 (above) show that crosslinked ethylene-based polymer compositions containing ethylene / MOCOS copolymers exhibit improved high temperature creep performance (i.e., shorter high temperature creep elongation %) than the comparative samples (control formulations). The data demonstrate the advantage of using ethylene / MOCOS copolymer compositions to achieve a desired crosslinking level.
[0127] IE34 (ethylene / (0.15 wt%) MOCOS copolymer, 0.6 wt% free (D Vi )4) of CS32 (LDPE and 0.75 wt% free (D Vi )4) Compared with IE34, the same (D Vi ) 4, weight percent (0.15 wt%), and the same amount of DCP (0.3 wt%) achieved better cure response including shorter T90 time (5.25 vs. 5.55), lower high temperature creep (85% vs. 143%), and higher MH-ML (2.50 vs. 2.41).
[0128] The present disclosure is not limited to the embodiments and examples contained herein, but is specifically intended to include portions of the embodiments and modified forms of those embodiments, including combinations of elements of different embodiments, within the scope of the following claims. Examples of the invention of this application include the following: [1] A process comprising: (A) providing an ethylene / MOCOS copolymer, the ethylene / MOCOS copolymer comprising: (i) units derived from ethylene, (ii) 0.01% to 0.5% by weight of units derived from a comonomer, and (iii) optionally, units derived from termonomers Including, The comonomer is represented by the formula (I) [R 1 ,R 2 SiO 2 / 2 ] n (In the formula, n is an integer of 3 or more, Each R1 are independently 2 ~C 4 ) alkenyl or H 2 C=C(R 1a )-C(=O)-O-(CH 2 ) m - and R 1a is H or methyl, m is an integer from 1 to 4; Each R 2 are independently H, (C 1 ~C 4 ) alkyl, phenyl, or R 1 is) providing an ethylene / MOCOS copolymer, the ethylene / MOCOS copolymer being a monocyclic organosiloxane (MOCOS) of the formula: (B) mixing a free radical initiator with (A) the ethylene / MOCOS copolymer to form a mixture; heating the mixture; and forming a crosslinkable ethylene / MOCOS copolymer composition; The process includes: [2] crosslinking the crosslinkable ethylene / MOCOS copolymer composition; and forming a crosslinked ethylene / MOCOS copolymer composition having a gel content greater than 70%; The process according to [1] above, comprising: [3] An ethylene / MOCOS copolymer is provided, comprising: providing an ethylene / MOCOS copolymer, wherein the MOCOS comonomer is selected from the group consisting of 2,4,6-trimethyl-2,4,6-trivinyl-cyclotrisiloxane, 2,4,6,8-tetramethyl-2,4,6,8-tetravinyl-cyclotetrasiloxane, 2,4,6,8,10-pentamethyl-2,4,6,8,10-pentavinyl-cyclopentasiloxane, and combinations thereof; The process according to [1] or [2] above, comprising: [4] mixing 3% to 0.3% by weight of the free radical initiator (B) with 97% to 99.7% by weight of the ethylene / MOCOS copolymer (A); Heating the mixture at a temperature of 70 to 90°C; curing the crosslinkable ethylene / MOCOS copolymer composition; and forming a crosslinked ethylene / MOCOS copolymer composition having a T90 of less than 5 minutes; The process according to any one of the above [1] to [3], comprising: [5] mixing 1.5% to 0.5% by weight of said free radical initiator (B) with 98.5% to 99.5% by weight of an ethylene / MOCOS copolymer (A) having units derived from 0.3% to 0.5% by weight of said MOCOS comonomer; Heating the mixture at a temperature of 70 to 90°C; forming a crosslinkable ethylene / MOCOS copolymer composition; curing the crosslinkable ethylene / MOCOS copolymer composition; and forming a crosslinked ethylene / MOCoS copolymer composition having a high temperature creep elongation of 20% to 50%; The process according to any one of the above [1] to [4], comprising: [6] mixing 1.5% to 0.5% by weight of said free radical initiator (B) with 98.5% to 99.5% by weight of an ethylene / MOCOS copolymer (A) having units derived from 0.05% to 0.2% by weight of said MOCOS comonomer; Heating the mixture at a temperature of 70 to 90°C; forming a crosslinkable ethylene / MOCOS copolymer composition; curing the crosslinkable ethylene / MOCOS copolymer composition; and forming a crosslinked ethylene / MOCoS copolymer composition having a high temperature creep elongation of 50% to 90%; The process according to any one of the above [1] to [5], [7] A crosslinkable ethylene-based polymer composition, comprising: (A) an ethylene copolymer, (i) units derived from ethylene, (ii) 0.01% to 0.5% by weight of units derived from a comonomer; (iii) optionally, units derived from termonomers Including, The comonomer is represented by the formula (I) [R 1 ,R 2 SiO 2 / 2 ] n (In the formula, n is an integer of 3 or more, Each R 1 are independently 2 ~C 4 ) alkenyl or H 2 C=C(R 1a )-C(=O)-O-(CH 2 ) m - and R 1a is H or methyl, m is an integer from 1 to 4; Each R 2 are independently H, (C 1 ~C 4 ) alkyl, phenyl, or R 1 is) and an ethylene copolymer, which is a monocyclic organosiloxane (MOCOS) of the formula: (B) a free radical initiator; and Including, A crosslinkable ethylene-based polymer composition, wherein the ethylene / MOCOS copolymer composition has a gel content of greater than 70% after crosslinking. [8] The crosslinkable ethylene-based polymer composition of [7] above, wherein the MOCOS comonomer is selected from the group consisting of 2,4,6-trimethyl-2,4,6-trivinyl-cyclotrisiloxane, 2,4,6,8-tetramethyl-2,4,6,8-tetravinyl-cyclotetrasiloxane, 2,4,6,8,10-pentamethyl-2,4,6,8,10-pentavinyl-cyclopentasiloxane, and combinations thereof. [9] (A) 97% to 99.95% by weight of the ethylene / MOCOS copolymer; (B) 3% by weight to 0.05% by weight of the free radical initiator; The crosslinkable ethylene polymer composition according to the above [7] or [8],
[10] An ethylene / MOCOS copolymer (A) having 98.5% to 99.5% by weight of units derived from 0.3% to 0.5% by weight of said MOCOS comonomer; 1.5% by weight to 0.5% by weight of the free radical initiator (B); Including, The ethylene / MOCOS copolymer composition has a high temperature creep elongation of 20% to 50% after crosslinking. The crosslinkable ethylene polymer composition according to any one of the above [7] to [9].
[11] The crosslinkable ethylene polymer composition according to any one of the above [7] to [9], an ethylene / MOCOS copolymer (A) having from 98.5% to 99.5% by weight of units derived from 0.05% to 0.2% by weight of said MOCOS comonomer; 1.5% by weight to 0.5% by weight of the free radical initiator (B); Including, The ethylene / MOCOS copolymer composition has a high temperature creep elongation of 50% to 90% after crosslinking. The crosslinkable ethylene polymer composition according to any one of the above [7] to [9].
[12] The MOCOS comonomer is 2,4,6,8-tetramethyl-2,4,6,8-tetravinyl-cyclotetrasiloxane and the ethylene / MOCOS copolymer is (i) Mw / Mn between 7.5 and 9.5; (ii) a vinyl content between 0.3600 / 1000 carbons and 0.6200 / 1000 carbons, and (iii) Trans content of 0.1000 / 1000 carbon atoms to 0.3100 / 1000 carbon atoms The crosslinkable ethylene polymer composition according to any one of the above [7] to
[11] ,
[13] The crosslinkable ethylene polymer composition according to any one of the above [6] to
[12] , further comprising an antioxidant.
[14] A crosslinked ethylene-based polymer composition formed from the crosslinkable composition according to any one of the above [1] to
[13] .
[15] An article comprising the crosslinked ethylene-based polymer composition according to
[14] above.
Claims
1. A process comprising: (A) providing an ethylene / MOCOS copolymer, the ethylene / MOCOS copolymer comprising: (i) units derived from ethylene, (ii) 0.01% to 0.5% by weight of units derived from a comonomer, and (iii) optionally, units derived from termonomers Including, The comonomer is represented by the formula (I) [R 1 ,R 2 SiO 2/2 ] n (In the formula, n is an integer of 3 or more, Each R 1 are independently 2 ~C 4 ) alkenyl or H 2 C=C(R 1a )-C(=O)-O-(CH 2 ) m - and R 1a is H or methyl, m is an integer from 1 to 4, Each R 2 are independently H, (C 1 ~C 4 ) alkyl, phenyl, or R 1 (It is) providing an ethylene / MOCOS copolymer, the ethylene / MOCOS copolymer being of the formula: (B) mixing a free radical initiator with (A) the ethylene / MOCOS copolymer to form a mixture; heating the mixture; and forming a crosslinkable ethylene / MOCOS copolymer composition; The process includes:
2. crosslinking the crosslinkable ethylene / MOCOS copolymer composition; and forming a crosslinked ethylene / MOCOS copolymer composition having a gel content greater than 70%; The process of claim 1 , comprising:
3. An ethylene / MOCOS copolymer is provided, comprising: said MOCOS comonomer being selected from the group consisting of 2,4,6-trimethyl-2,4,6-trivinyl-cyclotrisiloxane, 2,4,6,8-tetramethyl-2,4,6,8-tetravinyl-cyclotetrasiloxane, 2,4,6,8,10-pentamethyl-2,4,6,8,10-pentavinyl-cyclopentasiloxane, and combinations thereof; 3. The process according to claim 1 or 2, comprising:
4. mixing 3% to 0.3% by weight of said free radical initiator (B) with 97% to 99.7% by weight of said ethylene / MOCOS copolymer (A); heating the mixture at a temperature of 70-90° C.; curing said crosslinkable ethylene / MOCOS copolymer composition; and forming a crosslinked ethylene / MOCOS copolymer composition having a T90 of less than 5 minutes; The process according to any one of claims 1 to 3, comprising:
5. mixing 1.5% to 0.5% by weight of said free radical initiator (B) with 98.5% to 99.5% by weight of an ethylene / MOCOS copolymer (A) having 0.3% to 0.5% by weight of units derived from said MOCOS comonomer; heating the mixture at a temperature of 70-90° C.; forming a crosslinkable ethylene / MOCOS copolymer composition; curing said crosslinkable ethylene / MOCOS copolymer composition; and forming a crosslinked ethylene / MOCOS copolymer composition having a high temperature creep elongation of 20% to 50%; The process according to any one of claims 1 to 4, comprising:
6. mixing 1.5% to 0.5% by weight of said free radical initiator (B) with 98.5% to 99.5% by weight of an ethylene / MOCOS copolymer (A) having 0.05% to 0.2% by weight of units derived from said MOCOS comonomer; heating the mixture at a temperature of 70-90° C.; forming a crosslinkable ethylene / MOCOS copolymer composition; curing said crosslinkable ethylene / MOCOS copolymer composition; and forming a crosslinked ethylene / MOCOS copolymer composition having a high temperature creep elongation of 50% to 90%; The process according to any one of claims 1 to 4, comprising:
7. 1. A crosslinkable ethylene-based polymer composition comprising: (A) an ethylene copolymer, (i) units derived from ethylene, (ii) 0.01% to 0.5% by weight of units derived from a comonomer; (iii) optionally, units derived from termonomers Including, The comonomer is represented by the formula (I) [R 1 ,R 2 SiO 2/2 ] n (In the formula, n is an integer of 3 or more, Each R 1 are independently 2 ~C 4 ) alkenyl or H 2 C=C(R 1a )-C(=O)-O-(CH 2 ) m - and R 1a is H or methyl, m is an integer from 1 to 4, Each R 2 are independently H, (C 1 ~C 4 ) alkyl, phenyl, or R 1 (It is) and an ethylene copolymer, which is a monocyclic organosiloxane (MOCOS) of the formula: (B) a free radical initiator; and 1. A crosslinkable ethylene-based polymer composition comprising:
8. 8. The crosslinkable ethylene-based polymer composition of claim 7, wherein the MOCOS comonomer is selected from the group consisting of 2,4,6-trimethyl-2,4,6-trivinyl-cyclotrisiloxane, 2,4,6,8-tetramethyl-2,4,6,8-tetravinyl-cyclotetrasiloxane, 2,4,6,8,10-pentamethyl-2,4,6,8,10-pentavinyl-cyclopentasiloxane, and combinations thereof.
9. (A) 97% to 99.95% by weight of said ethylene / MOCOS copolymer; (B) 3% to 0.05% by weight of said free radical initiator; The crosslinkable ethylene-based polymer composition of claim 7 or 8, comprising:
10. an ethylene / MOCOS copolymer (A) having from 98.5% to 99.5% by weight of units derived from from 0.3% to 0.5% by weight of said MOCOS comonomer; 1.5% to 0.5% by weight of said free radical initiator (B); The crosslinkable ethylene-based polymer composition of any one of claims 7 to 9, comprising:
11. The crosslinkable ethylene-based polymer composition according to any one of claims 7 to 9, an ethylene / MOCOS copolymer (A) having from 98.5% to 99.5% by weight of units derived from from 0.05% to 0.2% by weight of said MOCOS comonomer; 1.5% to 0.5% by weight of said free radical initiator (B); The crosslinkable ethylene-based polymer composition of any one of claims 7 to 9, comprising:
12. the MOCOS comonomer is 2,4,6,8-tetramethyl-2,4,6,8-tetravinyl-cyclotetrasiloxane and the ethylene / MOCOS copolymer is (i) Mw / Mn from 7.5 to 9.5; (ii) a vinyl content of from 0.3600 / 1000 carbons to 0.6200 / 1000 carbons, and (iii) a trans content of from 0.1000 / 1000 carbon atoms to 0.3100 / 1000 carbon atoms. The crosslinkable ethylene-based polymer composition of any one of claims 7 to 11, having
13. The crosslinkable ethylene-based polymer composition of any one of claims 7 to 12, comprising an antioxidant.
14. A crosslinked ethylene-based polymer composition formed from the crosslinkable composition of any one of claims 7 to 13.
15. 15. An article comprising the crosslinked ethylene-based polymer composition of claim 14.
Citation Information
Patent Citations
JP1973024492B1
Silicone-containing polymer compound, resist material and method foe forming pattern
JP2002348332A
Polyolefin compositions for photovoltaic encapsulant films
WO2019000744A1